Antioxidant, anticholinesterase inhibitory potential and molecular docking of isolated bioactive compounds From callus of salvia santolinifolia (boiss) (Bangladesh Journal of Botany, 2026)
The chemical constituents used in the medical industry are primarily derived from medicinal plants. The medicinal plant Salvia santolinifolia contains chemicals with cytotoxic, antibacterial, and antifungal properties. Callus culture presents a viable alternative to ensure a consistent supply of raw materials throughout the year. We investigated three compounds: salvialactomine (1), pentatriacontanoic acid 1, 3-dihydroxyprophle ester (2), and 5-methylflavone (3), for their potential as antioxidants and anticholinesterase inhibitors. Compound 3 was the most effective at suppressing the acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes. Compounds 1 and 3 showed modest ABTS cation radical scavenging activity in the ABTS assay, while only 3 were active in the DPPH assay. Molecular docking investigations of the isolated compounds revealed different binding interactions inside the enzymes' binding pocket, supporting the bioactivity data. These findings suggest that 5-methylflavone (3) shows promise as a potential medication for Alzheimer's disease based on its strong activity against acetylcholinesterase and butyrylcholinesterase in both theoretical and experimental research.Bangladesh J. Bot. 55(1): 45-52, 2026 (March)